Oxidative dehydrogenation of ethylbenzene using nitrous oxide over vanadia-magnesia catalysts - Shiju, N. Raveendran; Anilkumar, Mettu; Gokhale, S. P.; Rao, B. Seshagiri; Satyanarayana, C. V. V. (Catalysis Science & Technology, 2011)
A series of V-Mg-O catalysts with different loadings of vanadia were prepared by the wet impregnation method and the effect of the local structure of these catalysts on the oxidative dehydrogenation of ethylbenzene with N(2)O was investigated. High styrene selectivity (similar to 97%) was obtained at 773 K. The characterization of catalysts with methods such as XRD, FTIR, UV-visible, TPR, NMR and Laser Raman spectroscopy suggested that magnesium orthovanadate is the predominant vanadium containing phase and the size of the orthovanadate domains increases with increasing vanadia loading. The rate of ODH of ethylbenzene per V atom increases with vanadia loading and reaches a maximum at 10 wt%. The specific activity, i.e. the conversion of ethylbenzene per unit surface area of the catalysts, also exhibited a maximum at a vanadia loading of 10 wt% leading to the conclusion that activity of these catalysts is due to the presence of very small domains of Mg(3)(VO(4))(2) on the surface of MgO rather than crystallites of bulk Mg(3)(VO(4))(2). The higher styrene yield in the presence of N(2)O can be ascribed to the ability of N(2)O to keep vanadium species at a higher oxidation state.

Towards improved activity and stability in RWGS reaction: Dispersed copper in mesoporous alumina matrix as a strategy for enhanced performance - Saju, Simi; Rajendran, Sivaraj; Oztas, Ulviye; Ruiz, Sergio Carrasco; Reina, Tomas Ramirez; Ghosh, Biplab; Sree, Sreeprasanth Pulinthanathu; Meena, Raghavendra; Li, Guanna; Bobadilla, Luis F.; Vinod, Chathakudath P.; Mathew, Thomas; et al. (Chemical Engineering Journal, 2025)
The development of highly performing Cu-based catalysts with high dispersion of Cu species in nanocrystalline form on a suitable oxide support is significant in reverse water gas shift (RWGS) reaction. We report a simple and robust one-pot sol-gel synthesis of mesoporous Al10-xCuxOy (m gamma-Al10-xCux-SG) catalysts with Cu species in a highly dispersed nanocrystalline form in the gamma-Al2O3 matrix and its high catalytic performance in RWGS reaction. The lack of long range structural order of copper species in m gamma-Al10-xCux-SG catalysts evidenced from Cu-K edge extended X-ray absorption fine structure (EXAFS) studies illustrates the fine distribution of copper species in mesoporous gamma-Al2O3 lattice. Activity study revealed that m gamma-Al10-xCux-SG catalysts showed significantly high CO2 conversion to CO and excellent catalytic stability compared to gamma-Al10-xCux-I prepared by conventional impregnation method. Mesoporous Al9Cu1 (m gamma-Al9Cu1) displayed a CO2 conversion of 45 % at 500 degrees C, which is about 2.8 times higher activity than conventional gamma-Al9Cu1-I catalyst with almost same Cu loading as that of m gamma-Al9Cu1 catalyst. Stability study at 500 degrees C over a period of 50 h revealed that m gamma-Al10-xCux-SG catalysts at low Cu loading (m gamma-Al9.9Cu0.1) showed excellent catalytic stability. The strong copper-alumina interaction in m gamma-Al10-xCux-SG catalysts with enhanced number of active sites at the copper-alumina interface as evidenced from field emission scanning electron microscope (FESEM), high-resolution transmission electron microscope (HRTEM), H2-temperature programmed reduction (H2-TPR), X-ray photoelectron spectroscopy (XPS), electrochemical characterization, and Cu-K edge EXAFS analysis enhances the activity and stability of the catalyst. Density functional theory (DFT) studies and the Operando DRIFTS-MS analysis of RWGS over m gamma-Al9Cu1 catalyst revealed that the mechanism of RWGS reaction to CO formation on m gamma-Al10-xCux-SG catalysts is preceded through the formation of a hydroxycarbonyl (OCOH) intermediate. The present synthesis strategy provides an opportunity for producing Cu-based catalysts with further enhanced activity and stability in RWGS reaction by suitable modification of the catalyst.